2023
DOI: 10.1177/20416695231163473
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal correspondences and interactions between texture and taste perception

Abstract: In recent years, awareness of the influence of different modalities on taste perception has grown. Although previous research in crossmodal taste perception has touched upon the bipolar distinction between softness/smoothness and roughness/angularity, ambiguity largely remains surrounding other crossmodal correspondences between taste and other specific textures we regularly use to describe our food, such as crispy or crunchy. Sweetness has previously been found to be associated with soft textures but our curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…When discussing pitch, have already evaluated its correspondence with tastes. In addition, crossmodal correspondences literature shows a strong relationship between tastes and visual-haptic features, where sweetness is related to curved shapes (Velasco et al, 2016b), creaminess (Carvalho et al, 2017) and softness (Pistolas & Wagemans, 2023), whereas sourness/saltiness/bitterness are related to sharpness/angularity (Velasco et al, 2016a). In such relationships, some studies have demonstrated emotional mediation (Chuquichambi et al, 2024;Salgado Montejo et al, 2015;Velasco et al, 2015).…”
Section: Tastesmentioning
confidence: 99%
“…When discussing pitch, have already evaluated its correspondence with tastes. In addition, crossmodal correspondences literature shows a strong relationship between tastes and visual-haptic features, where sweetness is related to curved shapes (Velasco et al, 2016b), creaminess (Carvalho et al, 2017) and softness (Pistolas & Wagemans, 2023), whereas sourness/saltiness/bitterness are related to sharpness/angularity (Velasco et al, 2016a). In such relationships, some studies have demonstrated emotional mediation (Chuquichambi et al, 2024;Salgado Montejo et al, 2015;Velasco et al, 2015).…”
Section: Tastesmentioning
confidence: 99%